2019
DOI: 10.1515/iral-2018-0362
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment in concept-based L2 grammar teaching: The case of German light verb constructions

Abstract: German light verb constructions are especially challenging for advanced L2 learners because of the abstract meaning of the different verbs and the high degree of lexico-grammatical variety. Acknowledging that language is a symbolic system representing humans’ perception of the world and is thus strongly linked to embodied experiences, this study explores the potential of bodily engagement in the form of multimedia animations for leveraging the learning of embodied concepts related to light verb constructions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Recent metaphor awareness-raising approach studies have evaluated the efficacy of animated visualisation in teaching German grammar, such as motion verbs (Roche & Scheller, 2008), passive voice (Arnett et al, 2019), case systems (Gradel, 2016), modal verbs (Kanaplianik, 2016), and light verbs (Suñer & Roche, 2019); and in teaching English, such as vocabulary (Sato et al, 2021) and degrees of politeness (Takimoto, 2021). All studies compared the metaphor awareness-raising and non-metaphorical instructional approaches without a control group (Arnett et al, 2019;Gradel, 2016;Kanaplianik, 2016;Roche & Scheller, 2008;Sato et al, 2021;Suñer & Roche, 2019) The studies by Gradel (2016) and Suñer and Roche (2019) compared the animated metaphor awareness-raising approach and teacher-directed traditional teaching approach.…”
Section: Animated Visualisation In the Metaphor Awareness-raising App...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent metaphor awareness-raising approach studies have evaluated the efficacy of animated visualisation in teaching German grammar, such as motion verbs (Roche & Scheller, 2008), passive voice (Arnett et al, 2019), case systems (Gradel, 2016), modal verbs (Kanaplianik, 2016), and light verbs (Suñer & Roche, 2019); and in teaching English, such as vocabulary (Sato et al, 2021) and degrees of politeness (Takimoto, 2021). All studies compared the metaphor awareness-raising and non-metaphorical instructional approaches without a control group (Arnett et al, 2019;Gradel, 2016;Kanaplianik, 2016;Roche & Scheller, 2008;Sato et al, 2021;Suñer & Roche, 2019) The studies by Gradel (2016) and Suñer and Roche (2019) compared the animated metaphor awareness-raising approach and teacher-directed traditional teaching approach.…”
Section: Animated Visualisation In the Metaphor Awareness-raising App...mentioning
confidence: 99%
“…Recent metaphor awareness-raising approach studies have evaluated the efficacy of animated visualisation in teaching German grammar, such as motion verbs (Roche & Scheller, 2008), passive voice (Arnett et al, 2019), case systems (Gradel, 2016), modal verbs (Kanaplianik, 2016), and light verbs (Suñer & Roche, 2019); and in teaching English, such as vocabulary (Sato et al, 2021) and degrees of politeness (Takimoto, 2021). All studies compared the metaphor awareness-raising and non-metaphorical instructional approaches without a control group (Arnett et al, 2019;Gradel, 2016;Kanaplianik, 2016;Roche & Scheller, 2008;Sato et al, 2021;Suñer & Roche, 2019) The studies by Gradel (2016) and Suñer and Roche (2019) compared the animated metaphor awareness-raising approach and teacher-directed traditional teaching approach. Gradel (2016) explored the animated effects of the metaphor awareness-raising approach on learners of German as a foreign language studying case systems, through explicit instruction followed by interactive animation tasks, whereas Suñer and Roche (2019) analysed the animated effects of a metaphor awareness-raising approach on French learners of German studying light verbs, through explicit instruction followed by multimedia animations.…”
Section: Animated Visualisation In the Metaphor Awareness-raising App...mentioning
confidence: 99%
See 2 more Smart Citations
“…It applied not only to inflective words, but also to agglutinative ones. Other LVCs studies revealed formal semanticsbased descriptions of semantic aspects (Cordeiro & Candito, 2019;Georgescu, 2013;Hrenek, 2019;Ong & Rahim, 2021;Srinivas & Legendre, 2022;Suñer & Roche, 2021). From this point of view, the central suggestion was to think of LVCs as semantic rather than morphological units.…”
Section: Introductionmentioning
confidence: 98%